Dissipative Exciton Dynamics in Light-Harvesting Complexes - Schröter, Marco; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Spektrum, 2015)
Marco Schröter investigates the influence of the local environment on the exciton dynamics within molecular aggregates, which build, e.g., the light-harvesting complexes of plants, bacteria or algae by means of the hierarchy equations of motion (HEOM) method. He addresses the following questions in detail: How can coherent oscillations within a system of coupled molecules be interpreted? What are the changes in the quantum dynamics of the system for increasing coupling strength between electronic and nuclear degrees of freedom? To what extent does decoherence govern the energy transfer properties of molecular aggregates?.
Dissipative Quantum Dynamics -- Energy Transfer in Light-Harvesting Complexes -- The Rostock HEOM Package.
Keywords: Atoms; Physics; Mathematical physics; Physical chemistry; Atomic, Molecular, Optical and Plasma Physics; Theoretical, Mathematical and Computational Physics; Physical Chemistry